TEM Characterization of Helium Bubbles in T91 and MNHS Steels Implanted with 200 keV He Ions at Different Temperatures - 王霁 高星 王志光 魏孔芳 姚存峰 崔明焕 孙建荣 李炳生 庞立龙 朱亚滨 骆鹏 常海龙 张宏鹏 朱卉平 王栋 杜洋洋 谢二庆 (Chinese physics letters, 2015)
Modified novel high silicon steel （MNHS, a newly developed reduced-activation martensitic alloy） and commercial alloy Tgl are implanted with 200 keV He2＋ ions to a dose of 5 × 1020 ions/m2 at 300, 450 and 560~C. Transmission electron microscopy （TEM） is used to characterize the size and morphology of He bubbles. With the increase of the implantation temperature, TEM observations indicate that bubbles increase in size and the proportion of ＇brick shaped＇ cuboid bubbles increases while the proportion of polyhedral bubbles decreases in both the steel samples. For the samples implanted at the same temperature, the average size of He bubbles in MNHS is smaller than that in T91. This might be due to the abundance of boundaries and precipitates in MNHS, which provide additional sites for the trapping of He atoms, thus reduce the susceptibility of MNHS to He embrittlement.